Herpes Simplex Virus Thymidine Kinase Mutations Associated with Resistance to Acyclovir: a Site-Directed Mutagenesis Study - Frobert, E. (American Society for Microbiology, 2005)
Mutations in the thymidine kinase (TK) gene of herpes simplex virus (HSV) may confer resistance to acyclovir (ACV). Because of the high genetic polymorphism of this gene, discriminating between mutations related to resistance and mutations related to gene polymorphism can be difficult, especially when no sensitive strain has been previously isolated from the same patient. To assess the role of the mutations located at codons 51, 77, 83, and 175, previously detected in HSV-1 clinical isolates (F. Morfin, G. Souillet, K. Bilger, T. Ooka, M. Aymard, and D. Thouvenot, J. Infect. Dis. 182:290-293, 2000), in the acquisition of resistance to ACV, four mutants with site-directed mutations at these respective codons were constructed. The enzymatic activity of the proteins, produced using both a reticulocyte lysate system and a bacterial system, was evaluated using [(3)H]thymidine as substrate. This site-directed mutagenesis revealed that mutations at codons 51, 83, and 175 induce a loss of HSV-1 TK activity and are thus clearly involved in the acquisition of resistance to ACV. On the other hand, the mutation at codon 77 does not affect enzyme activity.